Microangiopathy underlying mixed-location intracerebral hemorrhages/microbleeds: A PiB-PET study. (19th February 2019) - Tsai, Hsin-Hsi; Pasi, Marco; Tsai, Li-Kai; Chen, Ya-Fang; Lee, Bo-Ching; Tang, Sung-Chun; Fotiadis, Panagiotis; Huang, Chen-Yu; Yen, Ruoh-Fang; Jeng, Jiann-Shing; Gurol, M. Edip
Abstract : Objective: To test the hypothesis that patients with concomitant lobar and deep intracerebral hemorrhages/microbleeds (mixed ICH) have predominantly hypertensive small vessel disease (HTN-SVD) rather than cerebral amyloid angiopathy (CAA), using in vivo amyloid imaging. Methods: Eighty Asian patients with primary ICH without dementia were included in this cross-sectional study. All patients underwent brain MRI and 11 C-Pittsburgh compound B (PiB)-PET imaging. The mean cortical standardized uptake value ratio (SUVR) was calculated using cerebellum as reference. Forty-six patients (57.5%) had mixed ICH. Their demographic and clinical profile as well as amyloid deposition patterns were compared to those of 13 patients with CAA-ICH and 21 patients with strictly deep microbleeds and ICH (HTN-ICH). Results: Patients with mixed ICH were younger (62.8 ± 11.7 vs 73.3 ± 11.9 years in CAA, p = 0.006) and showed a higher rate of hypertension than patients with CAA-ICH ( p < 0.001). Patients with mixed ICH had lower PiB SUVR than patients with CAA (1.06 [1.01–1.13] vs 1.43 [1.06–1.58], p = 0.003). In a multivariable logistic regression model, mixed ICH was associated with hypertension (odds ratio 8.9, 95% confidence interval 1.4–58.4, p = 0.02) and lower PiB SUVR (odds ratio 0.03, 95% confidence interval 0.001–0.87, p = 0.04) compared to CAA after adjustment for age. Compared to HTN-ICH, mixed ICH showed a similar mean age (62.8 ± 11.7 vs 60.1 ± 14.5 years in HTN-ICH) and risk factor profile (all p > 0.1). Furthermore, PiB SUVR did not differ between mixed ICH (values presented above) and HTN-ICH (1.10 [1.00–1.16], p = 0.45). Conclusions: Patients with mixed ICH have much lower amyloid load than patients with CAA-ICH, while being similar to HTN-ICH. Overall, mixed ICH is probably caused by HTN-SVD, an important finding with clinical relevance.